Pengaruh Biaya Operasional Dan Volume Penjualan Terhadap Laba Bersih Perusahaan Manufaktur Subsektor Makanan & Minuman Periode 2020-2023 - Intan Maulidiyah; Ade Sri Mulyani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Company sompetition is increasing, one of which occurs in companies in the food and beverage manufacturing sector. Companies compete to provide the latest innovation in each oh their products to increase profits. The aim of this research is to find out how much influence operational costs and sales volume have on net profit partially or simultaneosly. The population in this study was 95 manufacturing companies in the food and beverage subsector fot the 2020-2023 period. The sample selection used a purposive sampling technique of 30 companies with 4 period for a total of 120 samples. The data used is secondary data obtained from financial reports of food and beverage subsector manufacturing companies. The method used in this research is quantitative statistical research with a causality approach which aims to determine the causal relationship between the independent variable and the dependent variable by conducting hypothesis testing using SPSS version 27. The result of the research show that operational cost have a partial effect on net profit, sales volume have a partial effect on net profit, operational costs and sales volume simultaneosly influence net profit.